2012
DOI: 10.3389/fnins.2011.00145
|View full text |Cite
|
Sign up to set email alerts
|

Age-Based Differences in Strategy Use in Choice Tasks

Abstract: We incorporated behavioral and computational modeling techniques to examine age-based differences in strategy use in two four-choice decision-making tasks. Healthy older (aged 60–82 years) and younger adults (aged 18–23 years) performed one of two decision-making tasks that differed in the degree to which rewards for each option depended on the choices made on previous trials. In the choice-independent task rewards for each choice were not affected by the sequence of previous choices that had been made. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
95
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(111 citation statements)
references
References 72 publications
12
95
1
1
Order By: Relevance
“…In addition, the elderly adults demonstrated a similar FPE+ response in the right ventral striatum as the young, and the FPEQ model weighted FPE+ similarly for both groups, showing no differences in behavioral or neural responsiveness to counterfactual losses between groups. Previous research has demonstrated that healthy elderly adults are less affected by counterfactual outcomes (Brassen et al, 2012) and actually utilize decision making strategies that don't rely on reward predictions, such as win-stay-loseshift (Worthy & Maddox, 2012). The results of the model fitting shows that elderly adults SSIT performance was more likely to be guided by reward predictions than a strategy that doesn't utilize reward predictions.…”
Section: Disadvantageous Overweighting Of Counterfactual Gains In Thementioning
confidence: 66%
See 1 more Smart Citation
“…In addition, the elderly adults demonstrated a similar FPE+ response in the right ventral striatum as the young, and the FPEQ model weighted FPE+ similarly for both groups, showing no differences in behavioral or neural responsiveness to counterfactual losses between groups. Previous research has demonstrated that healthy elderly adults are less affected by counterfactual outcomes (Brassen et al, 2012) and actually utilize decision making strategies that don't rely on reward predictions, such as win-stay-loseshift (Worthy & Maddox, 2012). The results of the model fitting shows that elderly adults SSIT performance was more likely to be guided by reward predictions than a strategy that doesn't utilize reward predictions.…”
Section: Disadvantageous Overweighting Of Counterfactual Gains In Thementioning
confidence: 66%
“…Indeed, vmPFC activation is correlated with expected values, as it is in young adults, for older adults who perform more optimally (SamanezLarkin et al, 2011). Moreover, advanced age is associated with different decision-making strategies depending on the task contingencies (Worthy & Maddox, 2012) and older adults choice behavior is sometimes better explained by a win-staylose-shift (WSLS) strategy that does not rely on a reward prediction (Worthy & Maddox, 2012), as opposed to reinforcement learning strategies that do. This supports the notion that although the elderly use different decision-making strategies dependent on the task context, the vmPFC is important for processing reward predictions to guide choice behavior in some contexts.…”
mentioning
confidence: 99%
“…An example of this is highlighted in the paper by Worthy and Maddox (2012) that uses computational models of learning and decision making to identify strategy differences between younger and older adults. Consistent with previous studies of age differences in strategy use , Worthy and Maddox (2012) show that older adults use a simpler strategy (win-stay/lose-shift) compared to younger adults (who are better fit by a more traditional reinforcement learning model).…”
mentioning
confidence: 99%
“…The papers also cover a broad range of topics including reward effects on learning and memory, risky decision making, intertemporal choice, strategy use, and financial decision making in healthy adults (Gilbert et al, 2011;Mather and Schoeke, 2011;Samanez-Larkin et al, 2011a;Cavanagh et al, 2012;Mata et al, 2012;Shivapour et al, 2012;Spaniol and Wegier, 2012;Westbrook et al, 2012;Worthy and Maddox, 2012) along with a complementary study on susceptibility to misleading advertisements in individuals with frontal cortical damage .…”
mentioning
confidence: 99%
See 1 more Smart Citation